Pengembangan Model Pembelajaran Numerasi Bermakna Berbasis Visualisasi Mind Mapping pada Siswa Sekolah Dasar - Abdul Majid; Muh. Rochmat Muchson Santoso (Lembaga Yasin AlSys, 2026)
Although numeracy learning in elementary schools has received attention in various studies, research that specifically discusses the development of a meaningful numeracy learning model based on mind mapping visualization remains limited. This study aims to develop and evaluate the effectiveness of a mind mapping-based meaningful numeracy learning model in improving elementary school students’ numeracy skills. This study employed a quantitative approach with a Research and Development (R&D) design, involving 30 fifth-grade students of SDN 15 Bonto Jai, Pangkep Regency, who were selected through purposive sampling. Data were collected through expert validation questionnaires, learning outcome tests, observation, and interviews, and were then analyzed using descriptive quantitative techniques and the N-gain test. The results showed that the developed model obtained an average score of 3.72 and was categorized as very valid. The practicality test based on teacher and student responses reached 88.5%, which fell into the very practical category. In addition, the effectiveness test showed an improvement in students’ numeracy skills, with an average N-gain score of 0.68, which was in the moderate-to-high category. These findings indicate that the mind mapping visualization-based learning model is effective in helping students understand mathematical concepts in a more structured, systematic, and meaningful manner. The conclusion of this study affirms the importance of integrating visual media into numeracy learning as an innovative alternative for improving elementary school students’ numeracy skills, while also providing a theoretical contribution to the development of visual-based mathematics learning.